2019
DOI: 10.1051/e3sconf/201910000069
|View full text |Cite
|
Sign up to set email alerts
|

URANS and ACM for determining the aerodynamic performance of vertical-axis wind turbine

Abstract: This paper presents numerical results of a one-bladed vertical axis wind turbine using the k-ε RNG turbulence model. The rotor geometry was developed based on the research report available on the literature. The obtained results of aerodynamic blade loads and wake profiles downstream behind the rotor are in a good agreement with the experiment. This paper presents also the ability of calculating fluid flow parameters around the operating wind turbine by using the original approach – the actuator cell model (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Algorithms used in this work to solve governing equations were presented in previous work [61,62]. Transient calculations were performed using the sliding mesh technique available in ANSYS Fluent, Release 17.1 CFD code.…”
Section: Numerical Settingsmentioning
confidence: 99%
“…Algorithms used in this work to solve governing equations were presented in previous work [61,62]. Transient calculations were performed using the sliding mesh technique available in ANSYS Fluent, Release 17.1 CFD code.…”
Section: Numerical Settingsmentioning
confidence: 99%
“…In these investigations, transient analyzes of the operating VAWT were performed, therefore, the Unsteady Reynolds Averaged is approximately 0.2, the pressure-based solver was utilized in this work. Previous works (Rogowski et al, 2018 or Rogowski andHansen, 2019) have shown that the segregated algorithm available under the pressure-based solver provides a sufficiently accurate solution of aerodynamic characteristics of a VAWT, which is why it was also adopted in this work. This algorithm solves the governing transport equations sequentially, segregated from one another, moreover, the memory requirement for this algorithm is less than other algorithms.…”
Section: Numerical Settingsmentioning
confidence: 99%
“…The pressure-based solver also offers the possibility of choosing different velocity-pressure coupling methods and different discretization schemes. Following our own insights (Rogowski, 2018;Rogowski et al, 2018 or Rogowski andHansen, 2019) and recommendations of ANSYS Documentation (ANSYS, Inc.…”
Section: Numerical Settingsmentioning
confidence: 99%